Ultrasonographic examination of the patellar ligament after capsular and fascial imbrication for the treatment of cranial cruciate ligament rupture in dogs - Candela Andrade, Mario; Hoffmann, Senta Maria; Slunsky, Pavel; De Rus Aznar, Ignacio; Brunnberg, Leo (Frontiers in Veterinary Science, 2025)
IntroductionCranial cruciate ligament (CCL) rupture is the most common orthopedic condition in dogs, with many surgical options available for its treatment. Thickening of the patellar ligament after capsular and fascial imbrication (CFI) is a frequently reported complication, but its clinical significance remains unclear.MethodThis prospective study evaluated patellar ligament structural and thickness changes after CCL repair using CFI. Forty-six dogs with CCL ruptures treated at the Small Animal Clinic of Freie Universität Berlin between July 2013 and April 2015 were included. Clinical, radiographic, and sonographic assessments were performed pre-surgery and at 2–3 months and 8–10 months post-surgery. Parameters assessed included lameness scores, joint effusion, stability, extension pain, muscular atrophy, and arthritis. Uninjured contralateral joints from 20 dogs served as controls.ResultsPostoperative improvements included reduced lameness scores, joint effusion, instability, and extension pain. Patellar ligament thickness increased from 1.6 mm pre-surgery to 5.4 mm at 2–3 months, then decreased to 3.9 mm by 8–10 months. Structural changes peaked at the first follow-up (52.9%) and decreased by the second (6.4%). No significant correlations were found between ligament changes and clinical outcomes, patient demographics, or adjunct treatments like NSAIDs or physical therapy.ConclusionPatellar ligament alterations following CFI appear temporary and largely unrelated to clinical signs, patient factors, or treatment variables. These findings suggest that such changes do not significantly impact postoperative outcomes, underscoring the reliability of CFI as a treatment option for CCL rupture in dogs.